Aligning Mentorship Style With Beginning Teachers' Development: Contextual Supervision (Alberta Journal of Educational Research, 2000)
Contextual Supervision (CS), a developmental mentoring model recently designed, applied, and refined in a teaching internship setting in Western Canada, has been shown to be useful in providing guidance to the supervision of teacher-interns during their extended practicum. The present study (in which the author was a participant observer) provides further qualitative and quantitative evidence that illustrates the effectiveness of CS in guiding practicum supervisors in the task of helping beginning teachers to develop their instructional skills. It also suggests that the CS model can prove useful in supervisory practice with developing practitioners in a variety of instructional settings.